Tunable Magnetic Properties of Interconnected Permalloy Nanowire Networks - Escrig-Murua, J; Saavedra-Díaz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In this study, we investigate the magnetic properties of interconnected permalloy nanowire networks using micromagnetic simulations. The effects of interconnectivity on the hysteresis curves, coercivity, and remanence of the nanowire networks are analyzed. Our results reveal intriguing characteristics of the hysteresis curves, including nonmonotonic behaviors of coercivity as a function of the position of horizontal nanowires relative to vertical nanowires. By introducing horizontal nanowires at specific positions, the coercivity of the nanowire networks can be enhanced without altering the material composition. The normalized remanence remains relatively constant regardless of the position of the horizontal wires, although it is lower in the interconnected nanowire arrays compared to nonconnected arrays. These findings provide valuable insights into the design and optimization of nanowire networks for applications requiring tailored magnetic properties. © 2023 by the authors.
Keywords: magnetic properties; permalloy; interconnected nanowire networks; hysteresis curves